Twice Too Many: Dilemma in Managing a Patient With Recurrent Near-death Events in Primary Care - Fathima Begum Syed Mohideen; M. Radzniwan A. Rashid; Lim Mong Sai; Sharifah Najwa Syed Mohamad (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2026)
Tier 2